Analisis Pengaruh Dimensi Kualitas Jasa pada Loyalitas Pelanggan - Rita, Rita (Binus Business Review, 2011)
This study evaluates the influence of service quality on customer loyalty in motorbike and saloons hairdressing shops in Yogyakarta. The service quality is measured using five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The service quality is indeed considered the strongest competitive weapon by many organizations with respect to service. Sample is chosen utilizing purposive sampling method. 220 respondents of motorbike and 215 respondents of saloons hairdressing shops are employed. Data analysis is then conducted using regression analysis. This research finds that the five dimensions of service quality significantly influence the customer loyalty to employees and customer loyalty to the business. The dimension of tangibles strongly influences the customer loyalty to the business. To marketers, this finding provides for a long-term perspective of service management. In the conclusion, several suggestions for future research are given, which is to broaden service types so as to acquire higher generalization with more varied population.Â